Ø§Ù„Ø¥Ø´ÙƒØ§Ù„ÛŒØ© ÙÙŠ Ø§Ù„ØØ¯ÛŒØ« â€œØ¥Ù† Ø§Ù„Ù„Ù‡ Ø®Ù„Ù‚ Ø¢Ø¯Ù… Ø¹Ù„Ù‰ ØµÙˆØ±ØªÚ¾â€: Ø£Ø³Ø¨Ø§Ø¨Ú¾Ø§ ÙˆØÙ„ÙˆÙ„Ú¾Ø§ - Ramli, Angraini binti (Department of Hadis Sciences (IH), Faculty of Usuluddin, Adab, and Da'wah (FUAD), State Islamic Institute of Langsa (IAIN), 2018)
Hadith Innall?ha khalaqa Adam ?al? ??ratih, is one of hadith that has isyk?l (difficulties) or problems involving debates among scholars. Firstly, There are some scholars who argued that the problems in this hadith is because the pronunciation of ?al? ??ratih in this hadith is contrary to the Islamic faith. Secondly, Others argued that this hadith has a similarity with isr??iliy?t because in the Torah and the Gospel also found similar things in the creation of Adam. Thirdly, some scholars accept this hadith textually but interpreted it to another meaning in order fit with holiness of Allah. The fourth,opinion argue that damiror pronoun of words on ?al? ??ratih refer to Allah, either as interpretation the word of rahman or as an i??fah ta?r?fiyah and ikhti???iyah to Allah. The fifth, opinion argue that this damir refer to Adam. The sixth, opinion said that this damir returned to the owner face who was beaten as mentioned in the hadith is refer to the object which was hit, namely the face itself